CAMP/PKA-induced filamin A (FLNA) phosphorylation inhibits SST2 signal transduction in GH-secreting pituitary tumor cells. (28th October 2018) - Peverelli, E.; Giardino, E.; Mangili, F.; Treppiedi, D.; Catalano, R.; Ferrante, E.; Sala, E.; Locatelli, M.; Lania, A.G.; Arosio, M.; Spada, A.; Mantovani, G.
Abstract: An efficient intracellular response to somatostatin analogs (SSA) in pituitary tumors requires filamin A (FLNA). Since cAMP pathway plays an important role in GH-secreting pituitary tumors pathogenesis and FLNA is phosphorylated by PKA on S2152, aim of this study was to investigate in tumoral somatotrophs the impact of cAMP pathway activation and SSA stimulation on FLNA phosphorylation and the consequences on SST2 function. We found a PKA-mediated increase (2-fold) and SST2 agonist-induced decrease (−50%) of FLNA phosphorylation in GH3, GH4C1 and primary somatotroph tumor cells. This modification regulates FLNA function. Indeed, phosphomimetic S2152D FLNA mutant, but not phosphodeficient S2152A, abolished the known SSA antitumoral effects, namely: 1) inhibition of cell proliferation, reduction of cyclin D3 and increase of p27; 2) increase of cell apoptosis; 3) inhibition of cell migration via RhoA activation and cofilin phosphorylation. Coimmunoprecipitation and immunofluorescence assays showed that S2152A FLNA was recruited to activated SST2, whereas S2152D FLNA constitutively bound SST2 on the plasma membrane, but prevented Gαi proteins recruitment to SST2. In conclusion, we demonstrated that FLNA phosphorylation, promoted by cAMP pathway activation and inhibited by SSA, prevented SST2 signaling in GH-secreting tumoral pituitary cells. Highlights: PKA promotes, and SSA reduces, S2152 FLNA phosphorylation in tumoral somatotrophs. Phosphomimetic S2152D FLNA mutant abolishes SST2 antitumoral actions in GH3 cells. FLNA phosphorylation negatively regulates FLNA scaffold function for SST2 signaling. P-FLNA might be a new biomarker predicting GH-secreting tumors responsiveness to SSA.